2002
DOI: 10.4141/a02-011
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular immune responses of piglets after castration at different ages

Abstract: . 2002. Humoral and cellular immune responses of piglets after castration at different ages. Can. J. Anim. Sci. 82: 519-526. In this study, growth of piglets and their humoral and cellular immune responses were used to evaluate the effect of castration at different ages. Piglets (n = 84) from 14 litters were assigned to one of the six treatments: castration or sham-castration at 3, 10 or 17 d of age. An injection of bovine serum albumin (BSA) was given on the day of castration and a second one 14 d later. Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
1
8
0
3
Order By: Relevance
“…This age effect and a tendency for a treatment effect indicated that handling piglets 3 d after birth had a greater impact on serum IgG concentration as measured on d 5 after birth. It is possible that stress caused by processing procedures contributed to decreasing IgG in piglet blood at an age when colostrum-derived IgG is naturally decreasing (Martin et al, 2005) and the immune system of the piglets is not sufficiently developed to respond to antigenic stimulations (Lessard et al, 2002). Our results corroborate those previously reported in tilapia showing decreased plasma immuno-globulins (IgM) 1 to 5 d after a stressor (Chen et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…This age effect and a tendency for a treatment effect indicated that handling piglets 3 d after birth had a greater impact on serum IgG concentration as measured on d 5 after birth. It is possible that stress caused by processing procedures contributed to decreasing IgG in piglet blood at an age when colostrum-derived IgG is naturally decreasing (Martin et al, 2005) and the immune system of the piglets is not sufficiently developed to respond to antigenic stimulations (Lessard et al, 2002). Our results corroborate those previously reported in tilapia showing decreased plasma immuno-globulins (IgM) 1 to 5 d after a stressor (Chen et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…Because piglet castration may affect the immune system (Lessard et al, 2002) as well as behavior and stimulate activity of the adrenal axis (for review, see Prunier et al, 2006), the aim of the present study was to investigate the effect of castration on blood plasma concentrations of neopterin and biopterin in piglets where neopterin and biopterin were selected as biosensors of immune system activation. Neopterin and biopterin plasma concentrations were compared with cortisol as a marker of neuroendocrine activity, as well as to results of leukocyte profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Il a été montré chez le porc que la réponse humorale à l'injection d'un antigène est réduite lorsque la première injection a lieu le jour de la castration (LESSARD et al, 2002). Des études complémentaires sont néces-saires pour préciser les conséquences de la castration sur le fonctionnement du système immunitaire (inflammation, immunosuppression).…”
Section: Conclusion Et Perspectivesunclassified